2015
DOI: 10.1007/978-3-319-14367-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Metal Oxide Nanoparticle Powders

Abstract: Metal oxides are mainly used in powder or particulate form for their application as functional materials. Insights into functional as well as unwanted properties of different defect types ranging from oxygen vacancies to grain boundaries and pores require an integrated characterization approach and are extremely difficult to establish. After a brief introduction into the complexity of particle systems and related heterogeneities, we discuss examples where for defects and other distinct structural features of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 177 publications
0
16
0
Order By: Relevance
“…As a result, most nanoparticles deteriorate and transform into ill-shaped microcrystalline materials displaying very complex surface and interface characteristics. 14 The aim of the present study is to document the influence of oxygen in the surrounding continuous phase on the properties of as-synthesized metal oxide particles in comparison to those which were subjected to moderate annealing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, most nanoparticles deteriorate and transform into ill-shaped microcrystalline materials displaying very complex surface and interface characteristics. 14 The aim of the present study is to document the influence of oxygen in the surrounding continuous phase on the properties of as-synthesized metal oxide particles in comparison to those which were subjected to moderate annealing.…”
Section: Introductionmentioning
confidence: 99%
“…For nanoparticles with bare surfaces, nonradiative recombination can occur at surface dangling bonds or other types of defects that are associated with coordinatively unsaturated surface ions. 24 Related effects of the built-in potential suppress the radiative recombination of free excitons compared to the particles in water, where local potential effects and surface doping increase the PL intensity. 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…The still increasing interest in ZnO-based inorganic phosphors is clearly documented by the continuous rise in the number of publications related to the research topic ZnO nanoparticles and photoluminescence properties, as revealed by an up-to-date literature survey using Web of Science or other databases. A substantial body of work has established robust connections between photoluminescence excitation and emission properties of ZnO structures and different defect types contained therein. Although many optically and electronically active defects seem to be linked to the interfaces of ZnO nanostructures, systematic studies on the impact of nature and composition of the interface on the photoluminescence properties are scarce. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Vapor phase-grown particle powders of isolated anatase TiO 2 nanocrystals and decontaminated particle surfaces have proven to be an appropriate model system for the study of hydration-induced microstructural and electronic property changes [ 16 20 ]. Only recently, we have employed such particle powders as model systems for protein adsorption studies and attained a reproducible qualitative and quantitative assessment of the interaction of a model serum protein (bovine serum albumin, BSA) with compositionally and structurally well-defined particle agglomerates.…”
Section: Introductionmentioning
confidence: 99%